Pregnancy In Advanced Maternal Age: Perinatal Results - Ayala-Moreno, Dasio (2017)
Objective. To identify perinatal outcomes in pregnant women with advanced maternal age (EMA) treated at the NationalMaternal Perinatal Institute. Materials and methods. Observational, descriptive and retrospective study of 321 maternaloutgoings occurred during the period from January 1 to June 30, 2016.